Local governance in anticipatory action and crisis response: A new study in Mali - Bleck, Jamie; Gottlieb, Jessica; Kosec, Katrina; Kyle, Jordan; Soumano, Moumouni (International Food Policy Research Institute, 2023)
How best to deliver aid programs in fragile contexts and whether donors can support resilience in these contexts are long-standing questions among development practitioners and scholars. While there is widespread agreement that “local context” matters and should be taken into account when designing and delivering aid programs, it is difficult to know what aspects of local context matter and when, who to involve in locally driven decision-making (when there are myriad social and political forces), and how potential tradeoffs between competing preferences, needs, and priorities of local actors differ across space. Even when local context is beyond the influence of donors, a better understanding of local politi cal economy dynamics can help donors make better decisions and avoid unintended consequences.